RELATIONSHIP OF NITRATE AND PHOSPHATE CONCENTRATION ON PHYTOPLANKTON PRIMARY PRODUCTIVITY IN DUMAI RIVERS OF RIAU PROVINCE - Syafrizal, Syafrizal; Nurrachmi, Irvina; Efriyeldi , Efriyeldi (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Riau, 2021)
This research was conducted in January 2020 in the waters of the Sembilan Dumai River which aims to determine the concentration of nitrate and phosphate on the primary productivity of phytoplankton. The research method used in this research is the survey method while the determination of the research station was done by technic purposive sampling. The results showed that the average nitrate concentration ranged from 0.0194 - 0.0749 mg/l and the average phosphate concentration ranged from 0.1452 - 0.8502 mg/l. There are 6 classes of phytoplankton found in the waters of the Sembilan Dumai River, namely Bacillariophyceae, Cocinodiscophyceae, Chroococcophyceae, Cyanophyceae, Cyanobacteria and Xanthophyceae. The results of phytoplankton abundance calculations ranged from 74.07 - 280.09 Ind/L. The primary productivity value of phytoplankton for gross primary productivity ranged from 62.5 - 104.16 mgC/m2/jam, respiration values ​​ranged from 20.83 - 41.66 mgC/m2/jam and the net primary productivity value ranged from 41.67 - 72.91 mgC/m2/jam. The results of the multiple linear regression test for the relationship between nitrate and phosphate on the primary productivity of phytoplankton at each station are shown by the mathematical equation Y = 60.18 + (-233,19,35) x and Y = 60.18 + 30.44x with the coefficient of determination ( R2) = 0.140 and (R2) = 0.226 and the correlation coefficient (r) = 0.631, the mathematical equation states that the relationship between nitrate and phosphate on the primary productivity of phytoplankton is strong.